Teaching Learning Process Of Narrative Text At The First Year Of SMA Muhammadiyah 1 Pati: A Microetnography - Kusumaningrum, Dhika Ajeng (2012)
This research paper is aimed to describe the implementation of teaching narrative text at the first year of SMA Muhammadiyah. The objective of this study is to describe the classroom activities in the teaching-learning process of narrative text and to describe problem faced by teacher in the teaching learning process of narrative text. The writer tries to conduct a micro ethnographic research, because the researcher wants to to provide a description about teaching learning process of narrative text at SMA Muhammadiyah 1 Pati. In this research refers to teacher and student's behavior in teaching learning process at SMA Muhammadiyah 1 Pati. The writer collects data from observation in the class, interview with the teacher, and documentanalysis. The technique for analyzing data are reduction, description and conclusion or verification. The result shows that the syllabus to the first year students at SMA Muhammadiyah Pati is Contextual-Based Learning Curriculum (KTSP Curriculum). The general objective of teaching narrative in SMA Muhammadiyah 1 Pati are: the students can identify simple monologues form of narrative text, the students canrespond to simple monologue of narrative text, and the students can improve four skills . The media for teaching narrative text in SMA Muhammadiyah 1 Pati are the board and printed media. The teacher uses material in teaching learning process such as: textbook. The teacher uses some techniques in teaching narrative text. Those are oral techniques, discussion techniques, and giving task.. The teacher in SMA Muhammadiyah 1 Pati often used two pattern procedures at the classroom. The first is BKOF (Building Knowledge of Field), MOT (Modelling of Text), and ICOT (Independent Construction of Text). The second is BKOF (BuildingKnowledge of Field), MOT (Modelling of Text), and ICOT (Independent Construction of Text ), and JCOT (Joint Construction of Text). The teacher using evaluation in the end of study in the class. There are: commenting and mask and grades.